The mediating roles of psychological resilience and frustration tolerance in the relationship between coping styles and mood states of high-level basketball referees - Wang, Qiulin; Wang, Wei; Huang, Huanhuan; Wan, Binghui (Frontiers in Psychology, 2023)
Objective In order to promote the development of high-quality professional basketball referees in China, we explored the relationship between their coping styles and mood states during the game and assessed the contributions of psychological resilience and frustration tolerance to this relationship. Methods A total of 364 national and international male and female basketball referees were recruited and surveyed via the online questionnaire platform “Questionnaire Star”. All participants signed an informed consent form and completed the questionnaire. Common method bias test and Pearson correlation tests were used to analyze the study indicators, and the theoretical model for this study was validated using Process plug-in developed by Hayes. Results The results of the study showed that the coping style of the referees significantly predicted their psychological resilience, frustration tolerance, and mood state. Coping style enhanced psychological resilience (β = −0.30) and frustration tolerance (β = 0.38) and improved the mood states (β = 0.33) of the referees. In addition, coping style directly predicted mood state but also indirectly predict mood state through the intermediary variables of psychological resilience (β = 0.14) and frustration tolerance (β = 0.11), and the mediating effects accounted for 24.20 and 18.90% of the total effect, with psychological resilience playing a greater role than frustration tolerance. (β: standardized regression coefficient). Conclusion These findings suggest that when training high-level basketball referees, increasing the psychological indicators related to the coping styles and psychological resilience of high-level basketball referees can avoid their large emotional fluctuations and improve their accuracy in judging when facing unexpected events on the court.